Iron terephthalate metal organic framework derived rGO/Fe₂0₃/Ti0₂ thin film for photocatalytic degradation of Methylene blue dye in water - Hasmira Radde (2017)
The major limitations of the photocatalytic activity involving TiO2 photocatalyst are difficulty to isolate its powder from treated water, desorption of organic pollutants, high band gap energy and rapid recombination between the charge carriers (e-/h+ pairs). This study focuses on the modification of TiO2 thin film in order to obtain a better degree of degradation by incorporating small amount of iron terephthalate metal organic framework, MIL-53(Fe) and reduced graphene oxide, rGO to the titania thin film (as rGO/Fe2O3/TiO2 thin film). The rGO/ Fe2O3/TiO2 thin films were fabricated via dip coating technique onto a glass substrate. SEM images showed that the coating can be repeated up to 5 cycles and rGO smooth planar sheets were attached to the Fe2O3/TiO2 thin film. EDX analysis showed the presence of small amount of Fe3+ ions in TiO2 thin film. The effect of concentration of MIL-53(Fe), number of dip coating cycle and rGO content were evaluated through the photocatalytic degradation of methylene blue (MB) dye in water under UV-A light for 4 hours. It was found that the highest photocatalytic activity of MB could be obtained using concentration 0.005 wt% of MIL-53(Fe) with 5 dip coating cycles in 0.4 mg/mL of rGO content. This study revealed that the rGO/Fe2O3/TiO2 thin film exhibits a better photocatalytic degradation as it can degrade about 84.0% of 5 ppm MB in water under UV-A irradiation as compared to TiO2 thin film alone which can only degrade 68.5% MB. The total enhancement of the rGO/Fe2O3/TiO2 thin film was about 16%. The study on photocatalytic degradation of 5 ppm MB under visible light shows that rGO/Fe2O3/TiO2 able to degrade 46.7% of MB whereas TiO2 thin film alone was only 36.2%. A slight improvement which was about 10% of MB removal was obtained under visible light which means the incorporation of rGO has slightly reduced the band gap of TiO2 thin film. A better degree of degradation can also attributed to the better adsorption property of rGO/Fe2O3/TiO2 in comparison to that of TiO2 and Fe2O3/TiO2 thin film. In dark condition, rGO/Fe2O3/TiO2 thin film and TiO2 thin film alone can degrade 29.5% and 24.5%, respectively. About 5% enhancement was obtained in dark after incorporation of rGO and MIL-53(Fe). The rGO/Fe2O3/TiO2 thin film posses a good stability and can be reuse up to 3 cycles without activation. The performance of the rGO/Fe2O3/TiO2 thin film follows the pseudo-first-order reaction kinetic with the rate constant 0.007 min-1 which is almost double as compared to TiO2 thin film alone. The rGO/Fe2O3/TiO2 thin film has high potential to be applied in wastewater treatment field and also as a tinting material for households and industries to provide self cleaning property.